Deep Blue: Waterfire Saga #1 - Donnelly, Jennifer (Los Angeles ; New York : Disney-Hyperion, 2014)
Uncovering an ancient evil, Serafina, a mermaid of the Mediterranean Sea, searches for five other mermaid heroines who are scattered across the six seas, to save their hidden world.
Keywords: Mermaids -- Fiction; Supernatural -- Fiction; Magic -- Fiction; Good and evil -- Fiction